1 - Developing Contradictions: Diversity and the Future of the South African University - Kotecha, Piyushi (Journal of Higher Education in Africa, 2007)
The manner in which the contemporary university is represented evokes an ‘either/ or’ conceptualisation of the university as either staying loyal to the fundamentals of teaching, research and outreach, or a wholehearted participation in the neoliberalisation of higher education. This paper begins by questioning whether this dichotomy is as clear-cut as is suggested. It proceeds to examine the idea of a market-driven university as an Organisation for Economic Co-operation and De- velopment (OECD) construct in an attempt to highlight the very different context and challenges faced by a developing country like South Africa. At the most obvi- ous level, the objectives of the White Paper (1997) and the National Plan for Higher Education (2001) pointed to achieving both equity and efficiency simultaneously by increasing access to address apartheid’s legacy and increasing cost savings and streamlined functioning. This dual imperative placed on the South African univer- sity has the benefit of opening up the institution to a range of possibilities that are neither exclusively ivory tower nor entrepreneurial. The remainder of the paper intends to unpack what these roles, functions and identities could be for the future South African university.